Mobile Robotics at Your Fingertips: Smartphone-Controlled Educational Bot. - James, Hannah (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2023)
Mobile robotics has gained significant attention in both educational and research settings. This article presents an in-depth exploration of the "SmartBot," a cutting-edge smartphone-controlled educational robot designed to enhance robotics education and research opportunities. We delve into its key features, applications, and the potential impact it has on the field of robotics. Our main goal was to develop a lowcost mobile robot, which is cheaper than most commercial robots sold today and can find application not only in education and research, but also in other applications. This mobile robot was developed by designing and implementing a chassis having a Raspberry Pi controller programmed in C language in a Debian Linux-based OS that was used to control the chassis remotely via a Wi-Fi network. A mobile application was loaded into an Android smartphone with an easy-to-use graphical user Interface (GUI). Captured footages are sent wirelessly via Wi-Fi to the Android smartphone and it is stored in the local memory of the smartphone.